2016
DOI: 10.1590/1414-431x20165485
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of serum transforming growth factor-beta1 levels in patients with pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a poor 5-year survival rate of 5%. Biomarkers for the early detection of pancreatic cancer are urgently needed. Transforming growth factor-beta1 (TGF-β1) is elevated in the tissues and plasma of patients with PDAC. However, no studies systemically report prognostic significance of plasma TGF-β1 levels in PDAC. In the present study, we assessed the prognostic significance of serum TGF-β levels in patients with PDAC. TGF-β levels were determined in serum from 146 PDAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
(23 reference statements)
1
17
0
Order By: Relevance
“…Our previous studies have shown that TNF-α and TGF-β cytokines can upregulate ZIP14 levels in muscle cells [21]. These cytokines can be detected in the conditioned media of PDAC cell lines and sera of PDAC patients [9,[28][29][30][31][32]. It remains to be tested in future studies whether blocking TNF-α or TGF-β signaling in muscles can reduce Zip14 expression.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous studies have shown that TNF-α and TGF-β cytokines can upregulate ZIP14 levels in muscle cells [21]. These cytokines can be detected in the conditioned media of PDAC cell lines and sera of PDAC patients [9,[28][29][30][31][32]. It remains to be tested in future studies whether blocking TNF-α or TGF-β signaling in muscles can reduce Zip14 expression.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, they found that serum levels of TGF-β were significantly higher in PDAC patients than patients with benign pancreatic conditions. They also concluded that high levels of TGF-β were associated with increased tumor size, metastasis (lymphatic and distant), and higher tumor stage [ 89 ]. The five-year median overall survival was 21.7% in the low TGF-β group and 15.5% in the high TGF-β group ( p < 0.01) [ 89 ].…”
Section: Tgf-β/smad4 As a Prognostic Marker Of Pdacmentioning
confidence: 99%
“…CD40 has also been related to transforming growth factor beta 1 (TGF-β1) [ 28 ], another key protein implicated in angiogenesis, immune suppression, and cell migration [ 30 , 31 ] and proposed as a prognostic biomarker for PC. Thus, Zhao et al [ 32 ] found higher serum TGF-β1 concentrations in patients with PC than in patients with benign pancreatic disease or healthy controls and observed a correlation of this increase with more advanced tumor stage and metastasis.…”
Section: Introductionmentioning
confidence: 99%